GhPLP2 Positively Regulates Cotton Resistance to Verticillium Wilt by Modulating Fatty Acid Accumulation and Jasmonic Acid Signaling Pathway - Zhu, Yutao; Hu, Xiaoqian; Wang, Ping; Gao, Linying; Pei, Yakun; Ge, Zhaoyue; Ge, Xiaoyang; Li, Fuguang; Hou, Yuxia (Frontiers in Plant Science, 2021)
Patatin-like proteins (PLPs) have nonspecific lipid acyl hydrolyze (LAH) activity, which can hydrolyze membrane lipids into fatty acids and lysophospholipids. The vital role of PLPs in plant growth and abiotic stress has been well elucidated. However, the function of PLPs in plant defense response against pathogens is still poorly understood. Here, we isolated and identified a novel cotton (Gossypium hirsutum) patatin-like protein gene GhPLP2. GhPLP2 expression was induced upon treatment with pathogens Verticillium dahliae, Fusarium oxysporum, and signaling molecules jasmonic acid (JA), ethrel in cotton plants. Subcellular localization revealed that GhPLP2 was localized in the plasma membrane. GhPLP2-silenced cotton plants showed reduced resistance to V. dahliae infection, while overexpression of GhPLP2 in Arabidopsis enhanced the resistance to V. dahliae, with mild symptoms, decreased disease index, and fungal biomass. Hypersensitive response, callose deposition, and H2O2 accumulation triggered by V. dahliae were reduced in GhPLP2-silenced cotton plants. Overexpression of GhPLP2 in Arabidopsis results in the accumulation of linoleic acid (LA, 18:2) and α-linolenic acid (ALA, 18:3) and facilitates the biosynthesis of JA and JA-mediated defensive response. Consistently, GhPLP2 silencing in cotton plants reduces the accumulation of linoleic acid (LA, 18:2) and α-linolenic acid (ALA, 18:3) and suppresses the JA biosynthesis and JA-mediated defensive response. These results showed that GhPLP2 is involved in cotton resistance to V. dahliae by maintaining fatty acid metabolism pools for JA biosynthesis and activating the JA signaling pathway.